The Diversity of Waterbirds Species in Jatipapak Mangrove Ecosystem at Kucur Resort, Alas Purwo National Park, East Java - Siddiq, Arif Mohammad; Sulistiyowati, Hari; Wimbaningrum, Retno; Setiawan, Rendy; Qisti, Nissaul; Supriadi, Dudun (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
The study aims to determine the composition and diversity of waterbirds species in the Jatipapak mangrove ecosystem at Alas Purwo National Park (APNP). This research was conducted on September-October 2020 with terrestrial and marine surveys in three stations. Data collection includes the waterbirds species and the number of individuals of each species. Data analysis used species composition and diversity index (Shannon Wiener=H’). The results of the study obtained the existence of 837 individuals waterbirds consisting of seven families, 16 genera, and 23 species. The waterbird communities in this area are composed of 11 species of resident birds and 12 species of migratory birds. The diversity index of waterbird species obtained is 2.31 which means moderate level. Based on the conservation status, there were 22 species of waterbirds that were classified as least concern (LC) and one species namely the Lesser Adjutant (Leptoptilos javanicus) which was included in the Vulnerable (VU) category.ABSTRAK: Penelitian bertujuan untuk menentukan komposisi dan keanekaragaman spesies burung air di ekosistem mangrove Jatipapak di Taman Nasional Alas Purwo (TNAP). Penelitian ini dilakukan pada bulan September-Oktober 2020 dengan survei darat dan laut di tiga stasiun. Data yang dicatat meliputi spesies burung air dan jumlah individu setiap jenis. Analisis data menggunakan penentuan komposisi spesies dan indeks keanekaragaman jenis Shannon Wiener (H’). Hasil penelitian diperoleh 837 individu burung air yang terdiri dari 7 famili, 16 genus, dan 23 spesies. Komunitas burung air di kawasan ini terdiri dari 11 spesies burung penetap dan 12 spesies burung migran. Nilai indeks keanekaragaman jenis burung air yang diperoleh adalah 2,31 yang berarti dalam kategori sedang. Berdasarkan status konservasi, terdapat 22 spesies burung air yang tergolong least concern (LC) dan satu spesies yaitu bangau tongtong (Leptoptilos javanicus) yang masuk dalam kategori Vulnerable (VU).